'I was broken in so many different ways': The intersection of complex factors impacting homeless and at‐risk African American women's mental health and well‐being. (31st October 2021) - Graf, Maria del Carmen; Dressel, Anne; Schmitt, Marin; Deal, Emily; Pittman, Belinda; Lopez, Alexa; Kako, Penninah; Mkandawire‐Valhmu, Lucy
Abstract: African American women are at higher risk of poor mental ill health compared with other racial and ethnic groups in the United States. For low‐income and homeless African American populations, the risk of poor mental ill health is even higher. The purpose of our study was to learn what programmes at a long‐term transitional living centre helped at‐risk and homeless African American mothers to succeed on their own, in accordance with self‐identified goals. We conducted ten focus group interviews with 39 graduates of a long‐term transitional living centre located in a Midwestern city, and an individual interview with the founder of that centre ( N = 40). Our study was informed by Black Feminist Thought, Life Course Theory, and an instrumental case study design. Thematic analysis was used to identify patterns in the qualitative data collected. Findings pertaining to mental health included impacts of adverse childhood experiences, lack of social networks, child placement in foster care, and implications on self‐esteem and self‐worth. Our findings demonstrate the need for healthcare providers to take into account the intersecting factors facing African American women experiencing homelessness undergirded by systemic racism, which impacts their mental health and well‐being.